2018
DOI: 10.15406/mojt.2018.04.00110
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, antifungal and antibacterial potential of Leptadenia hastata stem-bark extract

Abstract: Objectives: The Plant of genus Leptadenia belongs to family of Asclepiadaceae and have been widely employed for controlling various disease. Objective of the present study was to do preliminary phytochemical screening, Antifungal and Antibacterial potential of Hexane stem bark extract of Leptadenia hastata.Methods: hastata extracts were evaluated for potential antifungal and antimicrobial properties. The stem-bark of the plant were extracted with five solvent of various polarity and then vaporized to give resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The extract showed higher significant antifungal activity Aspergillus niger and Aspergillus flavus at different concentration over the other pathogens (Isaac et al, 2018). The plant has been widely employed for controlling various disease like antifungal, antibacterial/antimicrobial among others (Isaac et al, 2018), the L. hastata extracts were evaluated for potential antifungal and antimicrobial properties, as the stem-bark was extracted with five solvents of various polarity for antimicrobial activity against Escherichia coli, Salmonella typhi, Staphylococcus aureus and Klebsiella pneumoniae (Bacteria) and Aspergillus niger, Aspergillus flavus, Candida tropicalis and Fusarium oxysporium (Fungi).…”
Section: Antimicrobial Activities Of L Hastatamentioning
confidence: 95%
See 2 more Smart Citations
“…The extract showed higher significant antifungal activity Aspergillus niger and Aspergillus flavus at different concentration over the other pathogens (Isaac et al, 2018). The plant has been widely employed for controlling various disease like antifungal, antibacterial/antimicrobial among others (Isaac et al, 2018), the L. hastata extracts were evaluated for potential antifungal and antimicrobial properties, as the stem-bark was extracted with five solvents of various polarity for antimicrobial activity against Escherichia coli, Salmonella typhi, Staphylococcus aureus and Klebsiella pneumoniae (Bacteria) and Aspergillus niger, Aspergillus flavus, Candida tropicalis and Fusarium oxysporium (Fungi).…”
Section: Antimicrobial Activities Of L Hastatamentioning
confidence: 95%
“…The report of Steve et al, (2012) shows that L. hastata extracts contain alkaloids, saponins, phenolic glycosides, tannins, flavanoids, proanthocyanidines and triterpenes (Steve et al, 2012). Research of Fasihuddin et al, (2018) showed that qualitative phytochemical analysis of the extract confirmed the presence of various phytochemicals like sterols, terpenoids, alkaloids, flavanoids, phenols, carbohydrates, tannins, proanthocyanidins and glycosides in the n-hexane extract, whereas saponins was found to be absent (Fasihuddin et al, 2018).…”
Section: Phytochemicals Of L Hastatamentioning
confidence: 99%
See 1 more Smart Citation
“…The Leptadenia hastata zinc oxide (ZnO) nanoparticle from Leptadenia hastata leaf water extract was tested by disc diffusion method on nutrient agar medium as described by [9]. The extract exactly 5mg was dissolved homogeneity in 5mL of methanol giving a stock solution of 1000 μg/mL.…”
Section: Preparation Of Test Samplesmentioning
confidence: 99%
“…The crude extract of Leptadenia hastata was used in the antibacterial studies to ascertain the activity of the extract. The plant extract was tested using agar disc method as reported by Isaac et al, 12 5mg of the extract was collect and dissolved homogeneity in 5ml of methanol (1000 μg/mL stock) as well as lower concentration of 25, 50,100, 250, 500 and 1000ppm were prepared as the test concentration.…”
Section: Preparation Of Test Samples For Antibacterial Studiesmentioning
confidence: 99%